1998
DOI: 10.1007/s002590050292
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of imaging photodynamic injury to tumours by high-resolution positron emission tomography

Abstract: One early effect of the treatment of tumours by the new modality photodynamic therapy (PDT) is a reduction in tumour glucose levels. We have employed the widely used positron-emitting glucose analogue flurorine-18 fluoro-2-deoxy-D-glucose ([18F]-FDG), to determine whether, in principle, PDT-induced injury might be delineated non-invasively and quantitatively by positron emission tomography (PET). The scanner was of the high-density avalanche-chamber (HIDAC) type with a resolution of 2.6 mm. Subcutaneous T50/80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 14 publications
0
11
0
4
Order By: Relevance
“…Imaging techniques that have been successfully demonstrated and often clinically implemented for PDT outcome assessment include computed tomography (CT), positron emission tomography (PET),190 angiography, MRI, fluorescence imaging, and optical coherence tomography (OCT).…”
Section: Imaging For Planning Assessment and Monitoring Of Photomentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging techniques that have been successfully demonstrated and often clinically implemented for PDT outcome assessment include computed tomography (CT), positron emission tomography (PET),190 angiography, MRI, fluorescence imaging, and optical coherence tomography (OCT).…”
Section: Imaging For Planning Assessment and Monitoring Of Photomentioning
confidence: 99%
“…In 1998, Moore et al190 used flurorine-18 fluoro-2-deoxy-D-glucose to demonstrate that PET can be used to follow both tumor volume and surviving fractions at short time periods with the same degree of accuracy as high-resolution MRI. Necrosis and surviving tumor volume have also been successfully followed with pre-PDT and post-PDT contrast CT in the pancreas,171 bladder,172,173 lung, and bronchial tube.…”
Section: Imaging For Planning Assessment and Monitoring Of Photomentioning
confidence: 99%
“…Positron emission tomography (PET) is widely used to study the physiology of many types of cancer. 3,4 Since tissue uptake of 18 F-fluorodeoxyglucose (FDG) depends on both blood flow and hexokinase activity, it can be a good probe to investigate the mechanisms of PDT that dependent on the two parameters. However, because FDG uptake depends on both, it is difficult to differentiate on the basis of FDG alone.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, CR cannot be confirmed solely on the basis of CT findings. It has been reported that with PET, qualitative changes in photodynamic effect can be shown and this may be used in determining results more accurately [21].…”
Section: Discussionmentioning
confidence: 99%